The origin, government and doctriens of the leading protestant churches in England and the United States - Strite, Mary Catherine (My University, 1905)
Introduction; Protestants is a term applied to the adherents of Luther, from their protesting against the decree passed by the Catholic States at the second Diet of Spices in 1529. Martin Luther was an Augustinian monk and a professor in the University of Wittenberg. In 1517 he attacked the sale of indulgences and wrote out series of ninety-five statements in regard to them. These, he posted on the Church door, and invited anyone interested in the matter to enter into a discussion with him on the subject. This, he believed, was very illy understood. In posting these theses, as they were called, Luther didn't intend to attack the Church, and had no expectation of creating a. sensation. The theses were in Latin and addressed only to scholars. It turned out, however, that every one, high and low, learned and unlearned, was ready to discuss the perplexing theme of the nature of indulgences. These theses were promptly translated into German, printed, and scattered throughout the land. The Protestants opposed the Roman Church chiefly because it first, raises tradition to the level of the Scriptures as a source of doctrine, second, it denies justification by faith alone, and third, it makes the Pope the spiritual ruler of the entire Christian Church. The leader of the Protestant movement in Switzerland was Ulrich Zwingli. The Zwinglians differed from the Lutherans on the doctrine of the Lord's Supper. The former considered it a memorial feast intended to cell vividly to mind the Saviour's death. The latter held that while transubstantiation is to be denied, Christ is actually received in the sacrament. This division of opinion weakened by Protestant power.
Citation: Strite, Mary Catherine. The origin, government and doctriens of the leading protestant churches in England and the United States. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Protestants; Reformation in Germany and England; Theses